Upaya Meningkatkan Kemampuan Kognitif Anak dalam Mengenal Angka 1–10 melalui Media Biji-Bijian di RA Darul Ulum Rejing Probolinggo - Hasanah, Musrifatul (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2025)
This study aims to enhance the cognitive abilities of early childhood learners in recognizing numbers 1–10 through the use of natural materials, specifically seeds, as instructional media. The research subjects consisted of 15 children in Group A at RA Darul Ulum Rejing, Tiris District, Probolinggo Regency, during the 2024/2025 academic year. The study employed a Classroom Action Research (CAR) methodology conducted in two cycles, each comprising the stages of planning, action implementation, observation, and reflection. Data were collected through observation, interviews, and documentation techniques. The findings indicate that the use of seed-based media significantly improved the children’s ability to recognize numbers. In the first cycle, 40% of the children were at the “beginning to develop” stage, while 13.3% had not yet developed adequately. After revisions and improvements were implemented in the second cycle, 73.3% of the children successfully achieved the expected indicators, with only 6.7% remaining at the “not yet developing” stage. These results demonstrate that seed-based natural materials are highly effective as concrete, engaging, and developmentally appropriate learning tools for enhancing young children’s cognitive understanding of numerical concepts.